2021
DOI: 10.1093/rheumatology/keab289
|View full text |Cite
|
Sign up to set email alerts
|

Are neutrophil extracellular traps the link for the cross-talk between periodontitis and rheumatoid arthritis physiopathology?

Abstract: Objectives Neutrophil extracellular traps (NETs) play a role in the pathogenesis of periodontitis and rheumatoid arthritis (RA). However, it remains poorly understood whether NETs participate in the cross-talk between periodontitis and RA. Herein, we investigated the production of NETs in individuals with periodontitis and RA and its association with clinical parameters. The impact of periodontal therapy on RA and NET release was also assessed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 43 publications
2
30
0
1
Order By: Relevance
“…In PD, NETs have been shown to accelerate the formation of periodontal pockets by promoting the inflammatory response (91) and may increase local soft and hard tissue destruction (92). Furthermore, a combined clinical study showed that periodontal treatment could lead to significant changes in circulating NETs, affecting clinical manifestations of other diseases (93). The formation of NETs was the most significant in the OP DEGs biological process in our study, suggesting that NETs also play an essential role in OP.…”
Section: Discussionsupporting
confidence: 53%
“…In PD, NETs have been shown to accelerate the formation of periodontal pockets by promoting the inflammatory response (91) and may increase local soft and hard tissue destruction (92). Furthermore, a combined clinical study showed that periodontal treatment could lead to significant changes in circulating NETs, affecting clinical manifestations of other diseases (93). The formation of NETs was the most significant in the OP DEGs biological process in our study, suggesting that NETs also play an essential role in OP.…”
Section: Discussionsupporting
confidence: 53%
“…Importantly, NETs play a role in the pathogenesis of periodontitis and RA ( 87 ). However, the mechanism of NET information in periodontitis is unclear.…”
Section: Receptors That Trigger Netosismentioning
confidence: 99%
“…In addition, there was a significant association in RA patients between the concentration of ACPAs and periodontal severity represented by plaque index, clinical attachment level, and number of pockets [ 85 ]. An important observation was made by Oliveira et al [ 86 ], who found an association between the concentration of circulating NETs, RA activity, and periodontal clinical parameters. Moreover, treatment of periodontal disease was significantly associated not only with the reduction of NET concentration but RA alleviation as well [ 86 ].…”
Section: Citrullination Nets and Pads In Chronic Diseasesmentioning
confidence: 99%
“…An important observation was made by Oliveira et al [ 86 ], who found an association between the concentration of circulating NETs, RA activity, and periodontal clinical parameters. Moreover, treatment of periodontal disease was significantly associated not only with the reduction of NET concentration but RA alleviation as well [ 86 ]. Besides ACPAs, anti-carbamylated protein antibodies were also significantly elevated in patients with RA and periodontitis compared to controls [ 87 ].…”
Section: Citrullination Nets and Pads In Chronic Diseasesmentioning
confidence: 99%